(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The post-colonial era has witnessed many African writers embarking on, among many activities, decolonisation, cultural regeneration and nation-building through their works of art. Whilst they have striven to reclaim the African’s dignity, integrity and humanity that s/he has lost through colonialism, the post-colonial era has again presented to the same writer, new challenges posed by life, among them; the HIV and Aids epidemic. Whilst many writers have been quite eloquent in conveying the experiences and effects of HIV and AIDS on the affected, what has remained elusive is the root causes of its transmission as well as ways of dealing with the epidemic. Blame has largely been shouldered on patriarchy, men and ‘their’ promiscuous behaviour on one hand, and Shona traditional customs on the other, both of which are largely victims of a new socio-economic order. The paper thus is an exposition of the social vision of selected Shona writers concerning the HIV and Aids epidemic. It seeks to establish if they have moved away from the popular yet mythical victim-blame to accord the epidemic a more holistic and informative gaze. It also seeks to ascertain whether the writers have suggested realistic and humane solutions in their works of art or they have adopted the popular but less realistic defeatist stance. The paper uses the socio-historical approach to ground its observations and arguments.